Comparative analysis of physico-chemical and sensory properties of selected sweeteners - Salvador, Jonathan Rey H.; Marte, Kristia May T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2012)
This study compared physico-chemical and sensory properties of commercially available alternative sweeteners: raw wild honey, muscovado and coco sugar against sucrose in terms of acceptability in its application as sweetener for instant iced-tea. The study was divided into four phases. In phase 1, comparison of the sweetness intensity of the three sweeteners against sucrose in same-calorie concentrations by sensory evaluation using a structured magnitude estimation scaling method had been done. Phase 2 involved developing and comparing descriptive flavor profiles for the three alternative sweeteners using a modified Quantitative Descriptive Analysis method of sensory evaluation. Phase 3 determined and compared the physico-chemical properties of the three sweeteners. For phase 4, each of three sweeteners was compared against sucrose in terms of perceived overall difference when incorporated in a food model system (instant iced tea). In aqueous solutions with same-calorie values (phase 1), the sweetness intensity was perceived by semi-trained panelists to be highest in sucrose, followed by muscovado, coco sugar and lastly, honey. However, using modified Quantitative Descriptive Analysis (phase 2), honey was perceived as sweeter than coco sugar. The discrepancy in perceived sweetness as indicated by the results in phase 1 and phase 2 is attributed to the difference in sugar concentration of coco sugar as is and honey as is. Sucrose content had been found to be highest in muscovado (89.5%) followed by coco sugar (86.96%) and honey (undetectable). Fructose and glucose content was highest in honey (32.94% and 39.56% respectively) followed by muscovado (2.18% and 2.79% respectively) and coco sugar (1.72% and 0.30% respectively). The sucrose content of the sweeteners had been positively correlated with the sweetness intensity in aqueous solution while the presence of a significant amount of fructose and glucose explained honey's perceived sweetness as is. In a food model system, The mean value of perceived difference from sucrose was highest in coco sugar (7.3/9, p (<0.05)), followed by muscovado (4.40/9, p(<0.05)) and lastly honey (3.76/9, p (<0.05)). Eaxh of the three sweeteners, flavor, and physico-chemical properties, so their uses as alternative sweeteners depend on the food system in which they will be incorporated in. The interaction between flavor compounds in the sweeteners and their effect on perceived sweetness and flavor should be further studied.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Sweeteners -- Analysis; Sugar substitute